Stream sediment contamination indexes in a U-enriched area - Antunes, Isabel Margarida Horta Ribeiro (2019)
The occurrence of Potential Toxic elements (PTE) in a river system is influenced by different factors such are geology, mineralogy, hydrology, chemical reactivity, land use, and biological activity. Around mine sites, the mineralogical content of the material exploited consists of inert materials from the gangue constituent’s mineralization or mineral constituents of rocks. Stream sediments are usually used as a tool for contamination evaluation and definition of PTEs enrichment clusters. The abandoned Picoto uranium mine area is located close to Viseu (central Portugal). The mine is in a soft slope area, with altitudes ranging from 360 to 380 m, and is cut by a stream that runs from Vilar Seco in the NW direction to the Cagavaio stream, in the NE-SW direction. Stream sediments were collected inside and outside the mine influence and Al, Fe, As, Cr, Cu, Mn, Pb, Sr, Th, U, W, and Zn contents were determined. Geoaccumulation index (Igeo), contamination factor (CF), and enrichment factor (EF) have been used in the assessment of the PTE contamination degree in stream sediments. The stream sediments are heavily to extremely contaminated in U and Th (Igeo=4-5) and moderately to heavily contaminated in As and W (Igeo=3-2). Contamination factor is moderate for Al, Cu, and Pb (1≤Cf<3), considerable for As and W (3≤Cf<6), and very high for U and Th (Cf≥6). The degree of contamination is very high (Cd = 50.6). The EF was also calculated using Al content as a reference value because it does not change significantly in stream sediments. Most stream sediments have significant enrichment in As, W, and U (EF=5-20) and are very highly enriched in Th (EF=20-40). The contamination of stream sediments from the Picoto area is due to erosion and leaching of the four mine dumps from the mine area. Furthermore, the contaminant concentrations tend to decrease downstream of the source, due to hydrodynamic and chemical processes in fluvial systems affected by the mine drainage.